Gender Negotiation in Pop Music: A Critical Discourse Analysis of Empowerment in “Power” by Little Mix ft. Stormzy - Hendy Nabil Rais (Fakultas Komunikasi, Sastra, dan Bahasa, 2025)
Pop music serves as a significant medium for gender representation, yet mainstream songs often reproduce patriarchal narratives that objectify women. This study examines how